Hardy Type Spaces Estimates for Multilinear Marcinkiewicz Operators - Liu, L. (Український математичний вісник, 2005)
The purpose of this paper is to prove the boundedness for some multilinear operators generated by Marcinkiewicz integral operators and Lipschitz functions on Hardy and Herz-Hardy spaces.